Membranoproliferative glomerulonephritis recurrence after kidney transplantation: using the new classification. Issue 1 (December 2016) - Alasfar, Sami; Carter-Monroe, Naima; Rosenberg, Avi; Montgomery, Robert; Alachkar, Nada
Abstract Background Membranoproliferative glomerulonephritis (MPGN) is an uncommon glomerular disorder that may lead to end stage renal disease (ESRD). With new understanding of the disease pathogenesis, the classical classification as MPGN types I, II, III has changed. Data on post-transplant MPGN, in particular with the newly refined classification, is limited. We present our center's experience of MPGN after kidney transplantation using the new classification. Methods This is a retrospective study of 34 patients with ESRD due to MPGN who received 40 kidney transplants between 1994 and 2014. We reviewed the available biopsies' data using the new classification. We assessed post transplantation recurrence rate, risk factors of recurrence, the response to therapy and allografts' survival. Results Median time of follow up was 5.3 years (range 0.5–14 years). Using the new classification, we found that pre-transplant MPGN disease was due to immune complex-mediated glomerulonephritis (ICGN) in 89 % of cases and complement-mediated glomerulonephritis (CGN) in 11 %. Recurrence was detected in 18 transplants (45 %). Living related allografts (P  = 0.045), preemptive transplantations (P  = 0.018), low complement level (P  = 0.006), and the presence of monoclonal gammopathy (P  = 0.010) were associated with higher recurrence rate in ICGN cases. Half of the patients with recurrence lost their allografts. The use of ACEi/ARB was associated with a trend toward less allograft loss. Conclusions MPGN recurs at a high rate after kidney transplantation. The risk of MPGN recurrence increases with preemptive transplantation, living related donation, low complement level, and the presence of monoclonal gammopathy. Recurrence of MPGN leads to allograft failure in half of the cases.